Brain gain in cognitive neuropsychology: Continuing commentary on Laine and Martin (2012), "Cognitive neuropsychology has been, is, and will be significant to aphasiology" - Pulvermueller, Friedemann (Aphasiology, 2012)
Cognitive neuropsychology celebrates important successes in both theoretical and translational research. These successes were, in many cases, due to successful integration of abstract cognitive information-processing accounts with neuroscientific wisdom, neuromechanistic theorising, and precise neurocomputational modelling. Neuron-cognition relationships are not only key to a better understanding of the true algorithms underlying language, memory, and thought, they are also at the heart of new translational advances, as exemplified by Dell's neuromechanistic cognitive model of aphasia recovery and treatment, and by new aphasic treatment techniques capitalising on the interactive (and non-modular) functional relationship between language and action systems proven by cognitive psychology and cognitive neuroscience research. Therefore, indeed, as Laine and Martin point out, cognitive neuropsychology remains attractive, but it does so chiefly because it is in the middle of what one might want to call its "neuronal turn".